Glutathione peroxidase-1 overexpressing transgenic mice are protected from cocaine-induced drug dependence. (March 2019) - Mai, Huynh Nhu; Chung, Yoon Hee; Shin, Eun-Joo; Kim, Dae-Joong; Sharma, Naveen; Lee, Yu Jeung; Jeong, Ji Hoon; Nah, Seung-Yeol; Jang, Choon-Gon; Kim, Hyoung-Chun
Abstract: Converging evidence has demonstrated that oxidative burdens are associated with drug dependence induced by psychostimulants. Here, we investigated whether oxidative stress directly mediates conditioned place preference and behavioral sensitization (drug dependence) induced by cocaine and whether glutathione peroxidase-1 (GPx-1), a major GPx, modulates cocaine-induced psychotoxic changes in mice. Cocaine-induced drug dependence was followed by increases in c-Fos-immunoreactivity (c-Fos-IR) in the nucleus accumbens. Simultaneously, cocaine significantly increased oxidative parameters and nuclear factor κB (NFκB) activity (i.e. nuclear translocation and DNA binding activity) in the striatum (including nucleus accumbens). Genetic depletion of GPx-1 made mice susceptible to drug dependence induced by cocaine in mice, while genetic overexpression of GPx-1 protected the mice from drug dependence. Pyrrolidine dithiocarbamate (PDTC), a NFκB inhibitor, significantly attenuated the sensitivity induced by the genetic depletion of GPx-1 in mice. However, PDTC did not exhibit any additive effects against the protection afforded by the genetic overexpression of GPx-1. Our results suggest that drug dependence induced by cocaine requires oxidative stress and NFκB activation, and that the GPx-1 gene is a potential protective factor against cocaine-induced drug dependence through positive modulation of NFκB. Graphical abstract: Image 1 Highlights: Treatment with cocaine resulted in a compensative induction of GPx-1. GPx-1 gene attenuated cocaine-induced oxidative potentials in the striatum. NFkB is a critical target for the GPx-1 activity against cocaine drug dependence.